2019
DOI: 10.14503/thij-17-6365
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Mass Index on Outcomes of Patients Undergoing Surgery for Acute Aortic Dissection: A Propensity-Matched Analysis

Abstract: To determine whether body mass index ≥30 kg/m2 affects morbidity and mortality rates in patients undergoing surgery for type A acute aortic dissection, we conducted a retrospective study of 201 patients with type A dissection. Patients were divided into 2 groups according to body mass index (BMI): nonobese (BMI, <30 kg/m2; 158 patients) and obese (BMI, ≥30 kg/m2; 43 patients). Propensity score matching was used to reduce selection bias. The overall mortality rate was 19% (38/201 patients)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 19 publications
0
35
1
Order By: Relevance
“…A propensity score-matched analysis found that obese (BMI, ≥30 kg/m 2 ) patients who underwent surgery for type A acute aortic dissection had higher postoperative mortality rates. Moreover, a previous report stated that obesity was significantly associated with increased risk of LCOS and other postoperative morbidities [27]. However, in our study, there was no significant correlation between BMI and LCOS risk after cardiac surgery in CHD children.…”
Section: Discussioncontrasting
confidence: 82%
“…A propensity score-matched analysis found that obese (BMI, ≥30 kg/m 2 ) patients who underwent surgery for type A acute aortic dissection had higher postoperative mortality rates. Moreover, a previous report stated that obesity was significantly associated with increased risk of LCOS and other postoperative morbidities [27]. However, in our study, there was no significant correlation between BMI and LCOS risk after cardiac surgery in CHD children.…”
Section: Discussioncontrasting
confidence: 82%
“…Thoracic aortic dissection (TAD) is a common and life-threatening aortic disease [1]. Despite improvements in medical therapy and surgical or endovascular techniques in recent years, TAD still has a high morbidity and mortality rate [2].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have investigated the impact of BMI in the prognosis of cardiac disease [10,11] , but the conclusions remain in dispute. The present study is innovative to demonstrate the impact of BMI on postoperative early adverse outcomes in Chinese AAAD patients undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Kreibich et al pointed out that obesity was not signi cantly associated with postoperative adverse outcomes in AAAD patients [11] . Lio et al reported that obese patients were more likely to develop postoperative mortality and adverse outcomes compared to non-obese patients [10] . Our ndings indicate that overweight and obese are at increased risk of postoperative early adverse outcomes in AAAD patients, which wasn't consistent with their studies.…”
Section: Discussionmentioning
confidence: 99%